2019
DOI: 10.1002/cncr.32677
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 study of LY3023414 in patients with advanced endometrial cancer harboring activating mutations in the PI3K pathway

Abstract: Background PI3K pathway activation is common in endometrial cancer. We evaluated the safety and efficacy of the dual PI3K/mTOR inhibitor, LY3023414, in patients with advanced endometrial cancer harboring activating mutations in the PI3K pathway. Methods We conducted a single‐arm phase 2 study of monotherapy LY3023414. Eligible patients had advanced endometrial cancer of any grade, prior management with 1‐4 cytotoxic lines, and PI3K pathway activation prospectively defined as a loss‐of‐function PTEN alteration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…LY3023414 is a novel oral PI3K/mTOR dual inhibitor designed for advanced cancer. It has recently completed a phase II clinical trial, 10 which demonstrated modest single-agent activity and a manageable safety profile in treating advanced endometrial cancer. However, little is known about its effect on bone modelling/remodelling, which will help to understand its potential effect on the skeletal system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LY3023414 is a novel oral PI3K/mTOR dual inhibitor designed for advanced cancer. It has recently completed a phase II clinical trial, 10 which demonstrated modest single-agent activity and a manageable safety profile in treating advanced endometrial cancer. However, little is known about its effect on bone modelling/remodelling, which will help to understand its potential effect on the skeletal system.…”
Section: Discussionmentioning
confidence: 99%
“… 9 LY3023414 subsequently showed modest single-agent activity and a manageable safety profile in treating advanced endometrial cancer in a phase II clinical study in March 2020. 10 Nevertheless, little is known about the function of LY3023414 in bone modelling/remodelling.…”
Section: Introductionmentioning
confidence: 99%
“…1), and it is an important signaling pathway for MDR in a variety of cancers, such as breast cancer, leukemia, lung cancer, ovarian cancer, hepatocellular carcinoma, and melanoma [7][8][9][10][11][12] . Many types of tumors often carry at least one change in PI3K [13][14][15][16][17] ( Table 1). The MDR phenotype often accompanies activation of the PI3K/AKT pathway, which renders a survival signal to withstand cytotoxic anticancer drugs and enhances cancer stem cell (CSC) characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Stable disease in 58% of patients was the best response reached and the pro-drug was found to be well tolerated [100] . XL765 (SAR245409) was tested in a first-in-human clinical trial to evaluate safety, maximum tolerated dose, PK, PD and efficacy; stable disease was achieved in 48% of patients with evaluable disease, supporting further development of XL765 [132] . Other Phase I clinical trials have since been completed with XL765 in solid tumors, including ovarian cancer, and lymphoma, as a monotherapy (NCT01587040; NCT01596270) or in combination with other agents, e.g., erlotinib (NCT00777699), and letrozole (NCT01082068).…”
Section: Dual Pi3k/mtor Inhibitorsmentioning
confidence: 99%